2018
DOI: 10.3389/fncel.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Modafinil Ameliorate the Neuroinflammation and Anxious Behavior in Rats during Sleep Deprivation by Inhibiting the Microglia Activation

Abstract: Background: Sleep deprivation (SD) plagues modern society due to the professional demands. It prevails in patients with mood and neuroinflammatory disorders. Although growing evidence suggests the improvement in the cognitive performance by psychostimulants during sleep-deprived conditions, the impending involved mechanism is rarely studied. Thus, we hypothesized that mood and inflammatory changes might be due to the glial cells activation induced modulation of the inflammatory cytokines during SD, which could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 95 publications
1
29
0
Order By: Relevance
“…Recently, growing lines of evidence had demonstrated that SD could trigger neuroinflammation and then resulted in neurobehavioral alterations including memory impairments (Xia et al, 2017;Zielinski et al, 2017). It was reported that pro-inflammatory cytokines such as IL-1β, TNF-α, IL-6 are found to be increased upon SD in humans as well as experimental animals, and activation of NF-κB was shown in cortex and hippocampus regions of CSD rat (Manchanda, Singh, Kaur, & Kaur, 2018;Wadhwa et al, 2018). NF-κB is sequestered in the cytoplasm and occupies a vital position in the inflammatory cascade; once under oxidative stress, it translocates into the nucleus and induces various inflammatory proteins such as iNOS and COX-2 (Qiao, Jiang, & Gao, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing lines of evidence had demonstrated that SD could trigger neuroinflammation and then resulted in neurobehavioral alterations including memory impairments (Xia et al, 2017;Zielinski et al, 2017). It was reported that pro-inflammatory cytokines such as IL-1β, TNF-α, IL-6 are found to be increased upon SD in humans as well as experimental animals, and activation of NF-κB was shown in cortex and hippocampus regions of CSD rat (Manchanda, Singh, Kaur, & Kaur, 2018;Wadhwa et al, 2018). NF-κB is sequestered in the cytoplasm and occupies a vital position in the inflammatory cascade; once under oxidative stress, it translocates into the nucleus and induces various inflammatory proteins such as iNOS and COX-2 (Qiao, Jiang, & Gao, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The role of microglia in sleep regulation remains elusive. Some studies reported that microglia are activated after sleep deprivation (Huang et al, 2014;Wadhwa et al, 2018;Wisor et al, 2011). Microglia activation is likely a consequence of sleep loss, however, rather than the cause of sleep rebound.…”
Section: Discussionmentioning
confidence: 99%
“…Astroglia become activated by inflammatory cytokines, such as IL-1β, and secrete several neurotoxic substances along with an enhanced GFAP protein expression. This enhanced GFAP expression relates to the astroglia activation severity [ 34 ]. However, strong activation of astroglia results in the secretion of a large number of chemokines, cytokines, ROS, and pro-inflammatory factors, further affecting the cellular state of surrounding cells, such as neurons, microglia, and astroglia themselves, thereby leading to excitotoxicity and neurodegeneration [ 35 ].…”
Section: Discussionmentioning
confidence: 99%